Malodorous volatile organic sulfur compounds: Sources, sinks and significance in inland waters. (4th March 2017) - Watson, Susan B.; Jüttner, Friedrich
Abstract: Volatile Organic Sulfur Compounds (VOSCs) are instrumental in global S-cycling and greenhouse gas production. VOSCs occur across a diversity of inland waters, and with widespread eutrophication and climate change, are increasingly linked with malodours in organic-rich waterbodies and drinking-water supplies. Compared with marine systems, the role of VOSCs in biogeochemical processes is far less well characterized for inland waters, and often involves different physicochemical and biological processes. This review provides an updated synthesis of VOSCs in inland waters, focusing on compounds known to cause malodours. We examine the major limnological and biochemical processes involved in the formation and degradation of alkylthiols, dialkylsulfides, dialkylpolysulfides, and other organosulfur compounds under different oxygen, salinity and mixing regimes, and key phototropic and heterotrophic microbial producers and degraders (bacteria, cyanobacteria, and algae) in these environs. The data show VOSC levels which vary significantly, sometimes far exceeding human odor thresholds, generated by a diversity of biota, biochemical pathways, enzymes and precursors. We also draw attention to major issues in sampling and analytical artifacts which bias and preclude comparisons among studies, and highlight significant knowledge gaps that need addressing with careful, appropriate methods to provide a more robust understanding of the potential effects of continued global development.